Analisis Perbandingan Abnormal Return dan Likuiditas Saham Sebelum dan Sesudah Stock Split - Elistarani, Putu Raras; Wijaya Kesuma, I Ketut (E-Jurnal Manajemen; Vol 3 No 10 (2014), 2014)
This study aims to determine differences in abnormal returns and liquidity of shares before-after stock split at companies listed Indonesian Stock Exchange. By using purposive sampling method then selected 25 samples of companies that meet the criteria. The period of observation for 5 days before - 5 days after stock split. Test of paired samples t-test showed the difference in average abnormal returns and liquidity of shares before- after stock split, this indicates that the market reacted positively to the stock split. Keywords: abnormal return, liquidity of shares, stock split, market reaction
Keywords: abnormal return, liquidity of shares, stock split, market reaction